How do Business Factors Affect Developers in Mobile Software Ecosystems? - Steglich, Caio; Marczak, Sabrina; Santos, Rodrigo; Mosmann, Luiz Henrique; Guerra, Luiz Pedro; De Souza, Cleidson; Figueira Filho, Fernando; Perin, Marcelo (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2020: Anais do XVI Simpósio Brasileiro de Sistemas de Informação, 2020)
Mobile Software Ecosystem (MSECO) is the kind of ecosystem in which developers build applications to attend the users of mobile technologies (e.g., Android and iOS). In an MSECO, the developers are responsible for the creation of new software solutions, and this drives the ecosystem profits. Therefore, we aimed to identify which business factors are considered important to developers and how they affect them to participate in an MSECO. To do so, we conducted: i) a Systematic Mapping Study to reach the MSECO studies regarding developers’ motivation; and ii) a Field Study to verify the findings based on interviews with 20 developers of mobile technologies. As a result, we found 12 business factors (e.g., Market Opportunities, Distribution Channels) that affect developers to adopt and participate in an MSECO, as well as some opinions about each factor. As an output, we aim to support developers regarding which factors may become important to them through the opinion of these business factors by other developers.